Feeding Jejunostomy: Is It a Safe Route in Pediatric Patients? Single Institution Experience - Fascetti-Leon, Francesco; El Agami, Hisham; Gobbi, Dalia; Clarke, Simon; Haddad, Munther; Choudhry, Muhammad (European Journal of Pediatric Surgery, 2018)
Introduction Impossibility to place a gastrostomy and failed gastroesophageal reflux surgery with unsafe swallow are the main indications to Feeding Jejunostomy (FJ) in children. The aim of this study is to quantify the incidence of complications associated with FJ.Materials and Methods A retrospective review of patients who had surgically inserted FJ between January 2009 and August 2013 at our institution was conducted. Data were obtained from medical records, operative notes, and radiology database, focusing on complications.Results A total of 19 patients, average age 39.6 months (3–168 months), were treated during the study period. Indications to FJ were gastroesophageal reflux disease (GERD) associated with unsafe swallow in 12, esophageal atresia in 5, and foregut dysmotility in 2. Seventeen FJ were inserted via laparotomy and 2 were laparoscopically assisted. In all cases, a serosal tunnel on the antimesenteric border was fashioned. No intraoperative complications were recorded. Tube dislodgement/blockage occurred on an average of 0.48 times per month in 18 out of 19 patients. The average radiation dose received for tube reinsertion/manipulation was 3.316 mSv/year/patient (0–10.66). Major postoperative complications occurred in 7 out of 19. After an average follow-up of 21 months, two have abandoned the use of FJ due to poor tolerance and three have fully weaned off. Two patients died due to unrelated causes.Conclusion FJ, as an alternative means for enteral feeding, may require multiple readmissions and exposure to radiological procedures. The high risk of severe complications should be considered when offering this procedure.
Keywords: postpyloric feeding; feeding jejunostomy; surgical jejunostomy; gastroesophageal reflux; gastrostomy